2007
DOI: 10.1111/j.1399-0012.2007.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of sirolimus in ganciclovir‐resistant cytomegalovirus infections in renal transplant recipients

Abstract: This suggests that the use of sirolimus plus ganciclovir therapy could be useful in ganciclovir-resistant CMV infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 20 publications
(24 reference statements)
1
40
0
3
Order By: Relevance
“…The occurrence of primary infection (CMV IgG serostatus; D+/R−) and the therapy of acute rejection have also been shown to predict CMV disease outcome (21)(22)(23). Thus, the intensity of the immunosuppressive therapy may influence the treatment of CMV Å sberg et al (24)(25)(26) and mTOR inhibitors may have direct anti-CMV effects (9,27,28 (17), and we have reported previously specific risk factors for recurrence and long-term outcomes in this study (29) (17). Effect of Immunosuppressive Therapy on CMV (Figure 2), also show significantly higher rates of (17,29).…”
Section: Cytomegalovirus (Cmv) Disease Is a Common Clinical Infectionmentioning
confidence: 99%
“…The occurrence of primary infection (CMV IgG serostatus; D+/R−) and the therapy of acute rejection have also been shown to predict CMV disease outcome (21)(22)(23). Thus, the intensity of the immunosuppressive therapy may influence the treatment of CMV Å sberg et al (24)(25)(26) and mTOR inhibitors may have direct anti-CMV effects (9,27,28 (17), and we have reported previously specific risk factors for recurrence and long-term outcomes in this study (29) (17). Effect of Immunosuppressive Therapy on CMV (Figure 2), also show significantly higher rates of (17,29).…”
Section: Cytomegalovirus (Cmv) Disease Is a Common Clinical Infectionmentioning
confidence: 99%
“…Sirolimus has antiviral properties and conveys a lower risk of CMV disease (24)(25)(26)(27); one prospective study of 1470 renal transplant recipients (55 of whom were kidney-pancreas transplant recipients) found that the use of sirolimus had a protective effect against CMV disease (odds ratio 0.27) (24), the Symphony trial also found a much lower rate of CMV in those on low dose sirolimus (6%) compared with those on standard or low cyclosporine Kotton A (15% and 11%) ([p = 0.003]) (28), and another trial noted that everolimus conveyed a reduction in the incidence of CMV infection, syndrome and viremia in de novo renal transplant recipients (29).…”
Section: Universal Prophylaxis and Preemptive Therapymentioning
confidence: 99%
“…Leflunomide alone or in combination with standard antiviral agents has shown some efficacy in transplant recipients refractory to current therapy (Avery et al 2010;Dunn et al 2013;Verkaik et al 2013). The combination of GCV and the immunosuppressive agent sirolimus for the treatment of GCV-resistant HCMV infections has led to a favorable outcome with respect to clinical status and graft rejection in kidney and kidney-pancreas recipients (Ozaki et al 2007). …”
Section: Management Of Infections Caused By Drug-resistant Hcmv Mutantsmentioning
confidence: 97%